Extrastriatal dopaminergic and serotonergic pathways in Alzheimer's disease: A 123I‐FP‐CIT study: Neuroimaging / New imaging methods. (7th December 2020) - Pilotto, Andrea; Caminiti, Silvia; Liguori, Claudio; Garibotto, Valentina; Presotto, Luca; Sala, Arianna; Turrone, Rosanna; Caratozzolo, Salvatore; Scalvini, Andrea; Rozzini, Luca; D'Amelio, Marcello; Mercuri, Nicola; et al.
Abstract: Background: Pathological reports suggest that dopaminergic and serotonergic pathways are early involved in Alzheimer's disease (AD). 123 I‐FP‐CIT SPECT imaging allows the evaluation of both dopamine transporter (DAT) and serotonin transporter (SERT) in several brain regions. Method: Alzheimer's disease patients were included in a multicenter study and underwent a standardized neurological examination, structural imaging and CSF, amyloid and metabolism imaging in order to reach a biomarker diagnosis of AD (i.e. A+T+N+ classification). Each patient underwent 123 I‐FP‐CIT SPECT imaging and the bindings of extrastriatal regions of interests were calculated from spatially normalized images. The occipital‐adjusted specific to non‐displaceable binding (SBR) in the different regions was compared between AD and controls adjusting for the effect of age, sex, disease duration and serotonergic/dopaminergic treatment. Result: 52 AD patients A+T+N+ and 75 controls entered in the study. AD patients showed lower 123 I‐FP‐CIT SPECT SBR in cingulate (p=0.001) and temporal lobe (p=0.007) as well as in insula (p=0.01) and thalamus (p=0.025) compared to controls. When dividing AD according to severity, MCI due to AD (n=17) showed significantly lower parietal SBR compared to controls (p=0.002) and significantly higher SBR in insula (p=0.01), thalamus (p=<0.001) and temporal lobe (p=0.008) compared to AD dementia (n=35). Conclusion: We demonstrated extrastriatal dopaminergic and serotonoergic impairment in Alzheimer's disease. In the parietal cortex the alterations was present already at MCI stage, while in the temporal regions, thalamus and insula alterations appeared later in the AD dementia stage. Longitudinal studies will be necessary in order to evaluate the clinical value of extrastriatal 123 I‐FP‐CIT SPECT assessment for possible different pattern of progression and response to treatment in AD patients.